PREFERENSI DAN FREKUENSI KONSUMSI MAKANAN JAJANAN PADA ANAK SEKOLAH DASAR DI KECAMATAN CIJERUK,KABUPATEN BOGOR - Leily Amalia; Oktavianus Para Endro; Rizal M Damanik (Food and Nutrition Society of Indonesia, 2012)
ABSTRACTThis study aimed to analyze preference and consumption frequency of street foods among elementary school children at Cijeruk sub-district, Bogor District. The design used as survey method at three elementary schools at the area, namely SDN 01 Palasari, SDN 02 Palasari, dan SDN 01 Cipicung. The data was collected in April until June 2012. The subjects of study were 80 students at 4th and 5th grade of elementary school, consisted of 40 boys and 40 girls. Data collection was done by observation and interview to students. The data collected were: family characteristics, individual characteristics, nutrition knowledge, preference and the reasons, and consumption frequency of the street foods. The results showed that family size of subjects mostly (65.5%) categorized as moderate (consisted of 4—6 persons). Both father’s and mother’s education level were categorized as low, namely graduated from elementary shools (42.5% each) and even ungraduated of elementary schools (31.3% and 23.8%). In general, family income per capita was categorized as poor (51.3%) and almost poor (40.0%), with average of Rp 183 063 which was lower than poverty line of West Java Province at sub-urban areas (Rp 210 000). The average of pocket money of subjects was Rp 2 293.7. Nutrition knowledge of subjects was generally categorized as moderate (47.5%). All of subjects stated that they like street foods. The order of street foods from high to low prefered by subjects was fruit, beverages, fried food, cakes, dried snack, and dish foods. The primary preference reason of subjects on street foods was taste (minimal 60% for each food group). The order of street foods which highly to rarely consumed per week was fried food (7.0 times), beverages (6.7 times), cakes (6.3 times), dish foods (6.2 times), salted-dried snacks (5.3 times), and fruits (5.0 times).Key words: consumption frequency, preference, reasons of preference, street foodABSTRAKPenelitian ini bertujuan untuk menganalisis preferensi dan frekuensi makanan jajanan pada anak SD di Kecamatan Cijeruk, Kabupaten Bogor. Penelitian dilakukan dengan metode survey, di tiga Sekolah Dasar di Kecamatan Cijeruk, Kabupaten Bogor, yaitu SDN 01 Palasari, SDN 02 Palasari, dan SDN 01 Cipicung. Pengambilan data dilakukan pada bulan April hingga Juni 2012. Subjek penelitian adalah siswa kelas 4 dan kelas 5 SD, berjumlah 80 siswa, terdiri dari 40 siswa laki-laki dan 40 siswa perempuan. Penarikan subjek dilakukan secara purposive proposional dari populasi siswa di ketiga SD terpilih. Data dikumpulkan dengan cara pengamatan dan wawancara kepada siswa, terdiri dari karakteristik keluarga, karakteristik individu, pengetahuan gizi, preferensi dan alasannya, serta frekuensi konsumsi makanan jajanan. Besar keluarga subjek sebagian besar (65.5%) tergolong sedang (4—6 orang). Pendidikan ayah dan ibu subjek sebagian besar tamatan SD (42.5%) dan tidak tamat SD (31.3% dan 23.8%). Pendapatan keluarga per kapita subjek umumnya tergolong miskin (51.3%) dan 40.0% termasuk kategori hampir miskin. Rata-rata pendapatan keluarga per kapita adalah Rp 183 063, lebih rendah dari garis kemiskinan Jawa Barat pedesaan (Rp 210 000). Rata-rata uang jajan subjek adalah Rp 2 293.7. Pengetahuan gizi subjek umumnya (47.5%) berada pada kategori sedang. Urutan makanan jajanan yang paling disukai hingga agak disukai adalah buah, minuman, makanan gorengan, kue, keringan asin, dan jajanan sepinggan. Alasan utama subjek dalam menyukai semua kelompok makanan jajanan adalah rasa (minimal 60%). Urutan kelompok jajanan dengan frekuensi konsumsi dalam seminggu dari tertinggi hingga terendah adalah makanan digoreng (7.0 kali), minuman (6.7 kali), kue (6.3 kali), jajanan sepinggan (6.2 kali), keringan asin (5.3 kali), dan buah (5.0 kali).Kata kunci: alasan suka, frekuensi konsumsi, makanan jajanan, preferensi